The effect of HAP addition on properties F-75 alloy fabricated via P/M 6 for biomaterial applications - Rohaya, Abdul Malek (Universiti Malaysia Perlis, 2011)
A Co-Cr-Mo (ASTM F-75) alloy is generally used because of their mechanical properties, good wear and corrosion resistance as well as biocompatibility. In order to obtain chemical similarity and interfacial bond form between implanted biomaterials and living tissue, addition of Hydroxyapatite (HAP) is required. This study has focused on a research on F-75 alloy mixed with HAP fabricated by powder metallurgy (P/M) technique. The effect of HAP addition ranging between 2 and 10 wt.% on biocompatibility, physical and mechanical properties were examined. During compaction, 500MPa of pressure was applied using uniaxial press machine. The samples were sintered into tube furnace at 1100˚C in argon atmosphere. The samples with dimensions of approximately 5mm in thickness and 19mm in diameter were produced. To analyse the result, the reference sample (F-75 alloy without HAP powder) and composites were compared. All the samples were tested to determine shrinkage, grain size, bulk density, apparent porosity, microhardness and corrosion test. For biocompatibility (corrosion test), all samples were immersed into simulated body fluid of 0.9% sodium chloride solution at 37˚C in 6-week duration. Every interval of 48 hours, the weight loss per area was recorded. By increasing amount of HAP, it is noticed that the composites were less shrink and grain size getting larger compared to the reference sample. The largest grain size was obtained for composite consists of 10 wt.% of HAP (32.56μm) meanwhile the smallest grain size was obtained for reference sample (21.43μm). These results are inversely proportional to the decreasing value of bulk density and microhardness. The result of apparent porosity closely to 30% is obtained due to the increasing amount of HAP. Higher result of apparent porosity is required for bone ingrowth purposes. For microstructure analysis, the composites microstructure showed agglomeration of HAP and pores scattered on the composite surface. Meanwhile, biocompatibility test has indicated that the corrosion rate are increasing due to addition of HAP except for composite that consists of 2 wt.% of HAP which has the lowest corrosion rate among others (2.53mpy). The possibilities that contribute to the increasing of corrosion rate as a function of HAP addition are; the formation of general attack and pitting between matrix and electrochemical solution used. Besides, the formation of apatite layer can be clearly seen on the composite surface as predicted. According to the results, composite contains 6 wt.% of HAP shows an interesting result for apparent porosity and corrosion resistance that can be correlated to the requirement of biomaterial applications.